A panorama in the university ministry for the definition and establishment of the institutional educational project of the USTA in Colombia - Arango Restrepo, Alvaro (University Santo Tomás, Bogotá, 2016)
This work presents a review of what in theory is meant by Campus Ministry, according to different looks within the Church, from the conception we have of college at Dominican-Thomistic tradition, through the vision offered by the university council documents Vatican II, to become what is thought by evangelizing presence in the university, according to papal documents that during the last two popes have been produced to guide the very exercise of this ministry.